Tree-based Water Footprint Assessment on Established Oil Palm Plantation in North Sumatera, Indonesia - Santosa, Edi; Stefano, Indra Mario; Gani Tarigan, Abdul Gani; Wachjar, Ade; Zaman, Sofyan; Agusta, and Herdhata (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2018)
ABSTRACTIn a long life cycle of oil palm plantation, sustainable water management is mandatory because irrigation is rarely applied. In order to develop water management for sustainable palm oil production, tree-based water footprint of well-established oil palm plantation was assessed. Field data were collected from February to June 2016 in Dolok Ilir managed by PTPN IV, North Sumatera, Indonesia. Additional data were obtained from interviews on the site and the surrounding estates, reports and references. Results showed that water footprint (WF) for production of fresh fruit bunch (FFB) was 510.69 m3 tonne-1 and crude palm oil (CPO) was 517.79 m3 tonne-1. Green, blue and grey water contributed 94.78%, 0.71% and 4.50% in FFB, and 93.48%, 1.66% and 4.85% in CPO productions, respectively. All green WF was calculated basen on actual value of tree evapotranspiration, therefore, the value was mostly lower than other researchs. Low amount of blue water indicates that the oil palm tree in North Sumatera extracts low amount of ground water. On the other hand, grey water for pollution dilution of fertilizers, pesticides and herbicides were high, i.e., 15.15 m3, 4.77 m3, 3.07 m3 tonne-1 FFB, respectively. It implies that reduction of grey water should be implemented in the near future through precission farming.Keywords: CPO, Elaeis guineensis, precission farming, sustainable production, water footprint